Trajectories of Care: Representations of Empowered Mothering in Contemporary Bollywood - Pramanik, Pratyusha; Mishra, Ajit K (SARE: Southeast Asian Review of English, 2023)
Mothering a child with disability increases caregiving responsibilities considerably, making the mother assume the role of the nurse, the therapist, and the educator. Uninterrupted care work, societal surveillance and prevalent stigma severely interfere with the mental, physical, and existential well-being of such mothers. Through a thematic analysis of select contemporary Bollywood films, this article maps the trajectories of care and examines the alternative mothering strategies adopted by mothers of children with disabilities to take care of their children and themselves. A critical examination of these on-screen mothers provides an insight into the shifting discourses of mothering practices in India.